Structural and Optical Properties of Copper Oxide Nanoparticles Synthesized by Chemical Precipitation Method - Ali Sabeeh Al-Jarah, Uday ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2025)
Sodium bicarbonate was used as a precipitation agent and copper nitrate as a precursor in the chemical precipitation process to create copper oxide nanoparticles (CuO-NPs). After that, scanning electron microscopy (SEM), X-ray diffraction (XRD), and ultra-violet (UV) microscopy have been used for characterizing the NPs. The prepared CuO-NPs showed crystalline and nanosize XRD patterns. The 26 nm crystallite size of the CuO NPs is confirmed by Scherer’s formula. According to the SEM image, the NPs have been spherical and tended of agglomerations. Copper oxide absorption spectrum at about 270nm is confirmed by the UV-visible.